he individual, society and power in the development of women’s education in the Russian Empire - T. E. Pokotilova; E. Yu. Oborsky (Гуманитарные и юридические исследования)
The article expands the scientific understanding of the history of the relationship and mutual influence of the formation process of the Russian system of women’s education with the development of civic engagement in the country. The study showed that the history of the development of women’s education in pre-revolutionary Russia is crucially connected with the active engagement of society in this direction in the person of both individual, most prominent and effective representatives of it, and united within the framework of non-political, primarily charitable, organizations. The tone in the formation of a certain system of women’s education was set by the authorities represented by, first of all, Catherine II and such members of the ruling house as Empresses Maria Feodorovna and Maria Alexandrovna. But, in the conditions of the obvious inability of the authorities to ensure the organization and development of a full-blooded education system in the country, women’s education becomes an object of application of the emerging public forces in the Russian Empire. The strength of the traditions of charity in the national culture, including the acceptance and official encouragement by the authorities of the charitable behavior of citizens, has led to a tangible immersion of many representatives of the propertied and educated segments of the population in social care for the creation and development of a women’s education system. At the same time, the constantly growing positive dynamics of the process was determined in many ways and obviously by a small number of other legitimate opportunities for selfrealization of people with an active lifestyle who voluntarily united for joint actions with charitable purposes. It is important that women themselves were one of the significant factors in the process. Thus, the country received powerful assistance in solving the problem of introducing more and more girls to education – future educators of new generations of Russians of all classes and potential participants in socio-economic relations. And, at the same time, by the actions described above, the socially active part of the Russian population participated in the creation of a system of horizontal ties and relations as the basis of its civil society.